Activated carbons as green and effective catalysts for generation of reactive radicals in degradation of aqueous phenol - Saputra, Edy; Muhammad, Syaifullah; Sun, Hongqi; Wang, Shaobin (Royal Society of Chemistry, 2013)
Several activated carbons (ACs) were used as metal-free catalysts for degradation of a toxic organiccompound, phenol, in the presence of different oxidants, H2O2, peroxydisulfate (PS) and peroxymonosulfate (PMS). It was found that ACs were effective in heterogeneous activation of PMS toproduce sulfate radicals for degradation of phenol, much better than H2O2 and PS. Particle size of AC significantly influenced AC activity, and powder AC was much more effective than granular AC. The complete phenol removal could be achieved in 15 min on powder activated carbon (PAC) under the conditions of [phenol] = 25 mg L-1, [PAC] = 0.2 g L-1, [PMS] = 6.5 mmol L-1, and T = 25 degrees Celcius. It was also found that phenol degradation was significantly influenced by PMS loading, catalyst loading, phenol concentration and temperature. Surface activation of PMS and phenol adsorption played important roles in phenol degradation. Surface coverage by intermediate adsorption and structural change induced deactivation of AC and catalytic activity could be partially recovered by regeneration using calcination.